Analisis E-Marketing, Effectiveness Of Advertising Dan Brand Awareness Terhadap Keputusan Pembelian - Yesi Umita Sari; Achmad Agus Priyono; Ita Athia (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research was conducted to analyze the effect of E-marketing, Effectiveness of advertising and Brand awareness on Khayrscarf Official. This research uses explanatory research with a quantitative approach. The source of data in this study is primary data derived from distributing questionnaires to Khayrscarf Official consumers and secondary data derived from documents, journals, previous research and other sources. The population used in this study was 154,600 taken from social media followers. The sampling technique in this study used purposive sampling and 100 samples were obtained using the method of randomly distributing questionnaires and the questionnaires distributed in this study used a Likert scale. Data were analyzed using multiple linear regression as measured by SPSS. Hypothesis testing using the t test and f test. The results showed that E-marketing, Effectiveness of advertising and Brand awareness had a simultaneous effect on purchasing decisions and partially E-marketing, Effectiveness of advertising and Brand awareness had a positive and significant effect on purchasing decisions. Keywords: E-marketing, Effectiveness of advertising dan Brand awareness